2019
DOI: 10.1016/j.jfluidstructs.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for computing the steady state fluid–structure interaction response of periodic problems

Abstract: A special type of fluid-structure interaction (FSI) problems are problems with periodic boundary conditions like in turbomachinery. The steady state FSI response of these problems is usually calculated with similar techniques as used for transient FSI analyses. This means that, when the fluid and structure problem are not simultaneously solved with a monolithic approach, the problem is partitioned into a fluid and structural part and that each time step coupling iterations are performed to account for strong i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In case of a periodic FSI problem, the periodicity can be used to get rid of the time step difference by using results from the same time step of a previous period. This coupling is called the time periodic coupling and has been described and investigated in previous work [16]. A time periodic coupling is the most obvious for the present work for several reasons.…”
Section: Time Step and Time Periodic Partitioned Fsimentioning
confidence: 89%
See 2 more Smart Citations
“…In case of a periodic FSI problem, the periodicity can be used to get rid of the time step difference by using results from the same time step of a previous period. This coupling is called the time periodic coupling and has been described and investigated in previous work [16]. A time periodic coupling is the most obvious for the present work for several reasons.…”
Section: Time Step and Time Periodic Partitioned Fsimentioning
confidence: 89%
“…Especially in case of a high ratio between fluid added mass and structural mass and an incompressible fluid, the solution process may not converge without a dedicated partitioned solution method [6]. Two of these partitioned solution methods have been investigated in a time step and time periodic framework in [16]. It has been shown that the Quasi-Newton inverse least squares (QN-ILS) method outperforms the Aitken under-relaxation method in any case.…”
Section: Partitioned Solution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FGDE-BEM model is the same as the FGDI-BEM model except that PROCAL solves only the disturbance velocity potential without the contribution of blade vibration velocities, φ, from the kinematic boundary condition of Equation (30). The blade vibration velocity and acceleration effects are included in the FSI analyses by means of the closed form expressions for fluid added mass and hydrodynamic damping.…”
Section: Fgde-bem Modelmentioning
confidence: 99%
“…The blade vibration velocity and acceleration effects are included in the FSI analyses by means of the closed form expressions for fluid added mass and hydrodynamic damping. The main advantage of this approach is that the fluid added mass and hydrodynamic damping can be explicitly included in the structural computation, which stabilizes the FSI solution and reduces CPU time [30].…”
Section: Fgde-bem Modelmentioning
confidence: 99%